Microstructure evolution and improved tribological properties of laser deposited Fe-36Ni alloy coating with B addition - Ke Gao; Haitao Jiao; Qiang Xu; Guimei Liu; Bin Peng; Dazhi Zhong; Mingming Mei; Zhenguang Liu; Zilong Zhao (Journal of Materials Research and Technology)
In this study, Invar alloy coatings with varying B content (1–6 wt%) were prepared by laser deposition to investigate the effects of B alloying on the microstructure, hardness, and wear resistance of coatings. The results indicated that the addition of B element refined the FCC dendritic of Invar alloy coating and promoted the formation of a Ni2B + FCC eutectic structure, significantly enhancing the hardness of coating to a maximum of 770.5 HV0.2. When the B content reached 1 wt%, the wear rate of the coating decreased by 83.6 %, and the friction coefficient was also markedly reduced. The wear mechanisms of the coatings vary with different B contents, transitioning from pure adhesive wear to adhesive wear accompanied by partial abrasive wear, and further evolving into a hybrid mechanism of abrasive wear and fatigue wear.